“Old” and “New” Trust in Higher Education - P. A. Ambarova; G. E. Zborovsky; N. V. Shabrova (Образование и наука)
Introduction. Today, the crisis of modern higher school and processes of its modernisation are followed by the crisis of institutional, inter-community and interpersonal trust, which has remained a fundamental basis of a high school system of vocational education for a very long time. The need to preserve trust as a fundamental basis and source of development of Russian higher education requires the study of its structural characteristics and understanding of the resource potential of trust by representatives of educational communities.The aim of the research was the sociological substantiation of actualisation in higher education of the old resource properties of trust and the emergence of new ones associated with the prospects of transition to a non-linear model of higher education.Methodology and research methods. The publication presents the results of theoretical and empirical sociological research, implemented with the use of theoretical positions and methodological principles of community and resource approaches, the theory of non-linear development of society. The empirical study was conducted using a mix strategy based on a combination of quantitative and qualitative methods, expert interviews, semi-formalised interview, focus-groups, content analysis and the method of secondary analysis of sociological data.Results and scientific novelty. The authors’ interpretation of the phenomenon of “old” and “new” trust in Russian higher education is presented. The novelty of the authors’ approach was to consider the problem of higher education not only within the framework of “educational” problems, but also in the broad context of social and socio-cultural changes, meaning the transition to a “liquid” postmodern society. The mobilisation possibilities for the constructive resolution of contradictions existing at the levels of institutional and inter-community relations and interactions in universities are shown. Practical significance. The research results have a positive significance not only for enrichment of the theory of higher education and social knowledge of non-material resources of its development. They are important to design various academic practical experience oriented on the use of resource properties of trust with a view to developing the social and human capital of high school communities as well as to elaborate new social technologies for managing the processes of trust formation in the university.